Perencanaan Pembelajaran Berbasis Nilai-nilai Moderasi Beragama - Sari, Mayang; Sari, Junaidah; Fauzan, Ahmad; Junaidah (Program Studi Manajemen Pendidikan Islam Fak. Ilmu Tarbiyah dan Keguruan, 2024)
SMAS Taman Siswa Teluk Betung is a pluralistic school that emphasizes religious tolerance through various religious, social, and tolerance activities, fostering a peaceful life based on individual tolerance. The aim of this study is to describe and analyze the planning of curriculum subjects based on religious moderation values at SMAS Taman Siswa Teluk Betung Bandar Lampung. This research uses a descriptive qualitative approach. Data collection techniques include observation, interviews, and documentation, followed by data analysis involving data reduction, data display, and data verification or conclusion. The results of this study indicate that the planning of learning based on religious moderation values has been well implemented, with the objective of cultivating commendable morals through psychomotor, cognitive, and affective assessments incorporating religious moderation values such as interfaith tolerance and actions against violence and promoting harmony. The learning strategy requires collaboration to achieve goals, necessitating mutual assistance and complementarity. Learning resources at SMAS Taman Siswa include facilities and infrastructure such as a prayer room. Classrooms are equipped with desks, chairs, lockers, LCDs, carpets, bulletin boards, fans, air conditioners, and more. Teachers allow the use of mobile phones during the learning process in accordance with regulations. Components of learning based on religious moderation values include lesson plans containing materials on tolerance, harmony, and avoiding acts of violence.